Eksistensi Wayang Golek pada Museum Wayang sebagai Ikon Atraksi Budaya Jawa Barat dalam Kawasan Pariwisata Kota Tua Jakarta - Syifana Mutiara Salsabila; Dyah Mustika Wardani; Gilang Fahreza (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Wayang Golek is one of Indonesia's traditional cultural heritages that represents the cultural identity of the Sundanese people. Beyond serving as a form of entertainment, it embodies historical, educational, moral, and philosophical values that have been passed down through generations. Through its performances, Wayang Golek conveys messages about ethics, leadership, social life, and humanity, making it a valuable medium for cultural education. However, the rapid advancement of information technology, the emergence of various forms of digital entertainment, and changes in modern lifestyles have contributed to a declining public interest in traditional performing arts. These circumstances present significant challenges to preserving the existence of Wayang Golek and maintaining its relevance, particularly among younger generations. Based on this background, this study aims to analyze the existence of Wayang Golek performances at the Wayang Museum as an iconic cultural attraction representing West Java within the Kota Tua Jakarta tourism area. The study employed a qualitative research approach, with data collected through field observations, in-depth interviews, and documentation. The research informants consisted of a bicycle rental service provider operating in the Kota Tua area and two visitors who directly attended the Wayang Golek performance. The collected data were analyzed descriptively to provide a comprehensive understanding of the role of Wayang Golek performances in preserving local cultural heritage, enhancing public appreciation of traditional arts, and strengthening the appeal of cultural tourism in the Kota Tua Jakarta heritage destination.